Fool's Gold? - Sargisson, L. author. aut Link
XI, 312 p.
Keywords: What's wrong with the world today and how might it become better (or worse)? These are the questions pursued in this book, which explores the hopes and fears, dreams and nightmares of the 21st century. Through architecture, fiction, theory, film and experiments with everyday life, Sargisson explores contemporary hopes and fears about the future.